Energy analysis of municipal waste in Dubrovnik - Paweł Król; Goran Krajačić (ACTA INNOVATIONS, 2018)
In each touristic city waste management system has to overcome the impact of visitors. Dubrovnik, famous as popular touristic destination, particularly notices tourists visiting city. Therefore potential impact of waste management in touristic cities, such as Dubrovnik, is presented. The paper includes estimation of yearly waste production by inhabitants and tourists visiting those city. Waste digestion is a method for biogas production. On the basis of the preceding estimation combined-cycle installation generating heat and electricity is proposed. The model combines Brayton cycle with low temperature Kalina model based on Rankine cycle. Literature analysis presents state of the art in this field. The simulation is prepared in Cycle-Tempo. Numerical analyses lead to technical issues, which have to be taken into consideration during waste utilization with such installation. Thus benefits and threats are discussed. The presented analysis assesses the maximal electric gain, which subsequently should consider waste preparation and purification.